Manajemen Pembelajaran Pendidikan Anak Usia Dini dengan Metode Bercerita dalam Pengembangan Karakter : Studi Kasus Di TK.Nurul Huda Kec.Trimurjo Kab.Lampung Tengah - Bambang Ariyanto (Attractive : Innovative Education Journal, 2024)
Early Childhood Education is the first formal stage for young children, where they actively absorb information through visual and auditory experiences. Moral crises due to lack of supervision underscore the importance of instilling good character from an early age. This study aims to describe the management of early childhood education using storytelling methods for character development. Conducted at TK Nurul Huda, Trimurjo District, Lampung Tengah Regency, the research employs a qualitative descriptive approach with a case study design, gathering data through interviews, observations, and documentation. Findings reveal that the approach involves structured lesson planning, organizational task division among teachers, implementation through relevant storytelling, and assessment using various evaluation methods. In conclusion, the storytelling method at TK Nurul Huda proves effective in developing early childhood character, aligning with children's developmental needs and learning environment.